Assessment of palliative care in chronic hematological conditions in children in a tertiary care hospital - Sharma, Rakesh; Kaushik, Dipesh; Kumar, Pancham; Sood, Arvind; Sood, Ambika (International Journal of Contemporary Pediatrics, 2022)
Background: The aim of palliative care is most certainly the improvement of quality of life of patients suffering from various haematological diseases like leukaemia, haemophilia, thalassemia owing to the importance of palliative care in ensuring quality end-of-life care, provision of palliative care has been identified as an international human right. The objective of this study was to asses palliative care in chronic haematological conditions using Paediatrics palliative screening scale (PaPaS). Methods: 71 cases who fulfilled inclusion and exclusion criteria were included in the study for assessment of palliative care. Then, the data was analysed using the Statistical Package for Social Sciences (SPSS) software (version 13) and descriptive and interferential statistics were used. Results: In leukaemia patients the mean PaPaS score was reported to be 23.58 (SD: 7.43). Nineteen participants (61.29%) had a PaPaS score of >25 and 12 participants (38.71%) had PaPaS score of less than 25. In thalassemia patients the mean PaPaS score was reported to be 27.42 (SD: 6.54). Twenty participants (64.52%) had a PaPaS score of >25 and 11 participants or 35.48% had PaPaS score less than 25. In haemophilia patients the mean PaPaS score was reported to be 32.88 (SD: 4.94). Seven participants (87.5%) had a PaPaS score of >25 and only single participants or 12.5% had PaPaS score less than 25. In lymphoma patient the PaPaS score was 34. Conclusions: Chronic hematological diseases have lot of unmet needs of palliative care and study calls for creation of hospice and palliative care facility in all hospitals to meet the unmet needs of palliative care.